Desenvolvimento de método de preparo de amostras baseado no efeito Maxwell-Wagner e determinação de elementos terras raras por técnicas espectrométricas - Cruz, Sandra Meinen da (2017)
A new method for analytical applications based on Maxwell-Wagner effect with to use of microwave radiation in closed system is proposed. Considering the interaction of carbonaceous materials with an oscillating electromagnetic field in the microwave frequency range, a very fast heating is observed due to interfacial polarization that results in localized microplasma formation. Such effect was evaluated in a monomode microwave system and temperature was recorded using an infrared camera. For analytical applications, a closed reactor under oxygen pressure was evaluated for carbonaceous materials digestion. The combination of high temperature and oxidant atmosphere resulted in a very effective self-ignition reaction of sample, allowing its use as sample preparation procedure for further elemental analysis. In order to assure the feasibility of the proposed microwave-assisted self-ignition procedure, several parameters were evaluated using graphite sample, including the interaction of microwaves with the sample in pellet form or powder, in both open system at atmospheric pressure and into closed system under oxygen pressure (20 bar), and the maximum sample mass able to be completely digested. The rare earth elements (Ce, Dy, Er, Eu, Gd, Ho, La, Lu, Nd, Pr, Sm, Tb, Tm, Y and Yb) were determined by inductively coupled plasma optical emission spectrometry using ultrasonic nebulizer. After optimization, a sample mass of 400 mg was efficiently digested (residual carbon content lower than 1%) in a closed system using 4 mol L-1 HNO3 as absorbing solution. The accuracy of the proposed procedure was checked by neutron activation analysis and an agREEment better than 95% was achieved in comparison to microwave induced self-ignition results. Additionally, in this study a microwave-assisted extraction and dry ashing methods were performed and an agREEment better than 95 % (p>0.05) was obtained in both methods. The limits of quantification were in the range from 5 up to 70 ng g-1. Finally, the proposed procedure allows to use of high sample mass (400 mg) without to use of auxiliary reagent and also diluted absorbing solution.